Representasi Karakter Alpha Female Dalam Drama Korea Queenmaker - Hafifah, Dinda Hafid; Urfan, Noveri Faikar (Jurnal Pustaka Komunikasi, 2024)
Korean dramas or (Drakor) have become a global phenomenon, gaining widespread popularity around the world. They are recognized not only as entertainment but also as complex reflections of social dynamics. The presence of Alpha Female characters in Drakor signifies support for gender equality and indicates societal shifts in views on women's roles in various aspects of life. This study aims to understand the representation of Alpha Female characters in the Korean drama Queenmaker hoping to gain new insights into societal perceptions of women beyond the domestic sphere. Using a qualitative approach and Charles Sanders Peirce's semiotic analysis, the research found that Alpha Female characters exhibit leadership, confidence, and strength in facing challenges. From Peirce's perspective, these characters become important symbols that reinforce women's roles in fighting injustice and advocating for moral values. The findings underscore that Drakor is not just entertainment, but also a mirror of social realities that significantly influence perceptions of gender equality, expanding our understanding of women's roles in popular culture and the importance of gender equality in society.